Bosnia and Herzegovina : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2000)
This Selected Issues and Statistical Appendix paper on Bosnia and Herzegovina provides background information for the 1999 Article IV Consultation with Bosnia and Herzegovina. The economy has been dominated by a small number of large state-owned enterprises. A central policy was settled during the preparation of the privatization framework under which the competence to privatize was assigned to the entities. Major tax policy reforms will be needed over the medium term to address the deficiencies of the present tax system, and to lay the foundation for long-term economic growth, driven mainly by private sector development.